Pengaruh Inflasi, Tingkat Suku Bunga dan Ukuran Perusahaan Terhadap Return Saham pada Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2022 - Erfika, Natalia Riski; Rinofah, Risal; Maulida, Alfiatul (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine and analyze the influence of inflation, interest rates and company size on stock returns in the mining sector listed on the Indonesia Stock Exchange (BEI). The sample was 40 mining industry issuers listed on the Indonesia Stock Exchange (BEI) in the 2017-2022 period. The results of this research show that inflation and interest rates have a significant negative influence on stock returns, while company size has a significant positive influence on share returns in the mining sector listed on the Indonesia Stock Exchange (BEI).